Restructuring Regional Health Systems In Russia - Marquez, Patricio V.; Lebedeva, Nadezhda (World Bank, Washington, DC, 2012)
The delivery of health services in Russia is a federal, regional and municipal responsibility. Reform of the regional health systems, which suffer from over-reliance on curative and inpatient care, deteriorating infrastructure and equipment, and poor quality of services, is a major challenge for the country. From 2003-2008, the World Bank helped strengthen the stewardship capacity of Russia's Federal Ministry of Health and Social Development (MOHSD) and restructure health systems in two pilot regions: the Chuvash Republic and Voronezh oblast. In both regions, hospital bed numbers were reduced while simultaneously increasing service delivery capacity at the primary care, specialized ambulatory, and long-term care facility levels through the introduction of new technologies, clinical protocols, and resource allocation mechanisms that link payments to performance.